Implementing trials of complex interventions in community settings: The USC–Rancho Los Amigos Pressure Ulcer Prevention Study (PUPS). (April 2014) - Clark, Florence; Pyatak, Elizabeth A; Carlson, Mike; Blanche, Erna Imperatore; Vigen, Cheryl; Hay, Joel; Mallinson, Trudy; Blanchard, Jeanine; Unger, Jennifer B; Garber, Susan L; Diaz, Jesus; Florindez, Lucia I; et al.
Background: Randomized trials of complex, non-pharmacologic interventions implemented in home and community settings, such as the University of Southern California (USC)-Rancho Los Amigos National Rehabilitation Center (RLANRC) Pressure Ulcer Prevention Study (PUPS), present unique challenges with respect to (1) participant recruitment and retention, (2) intervention delivery and fidelity, (3) randomization and assessment, and (4) potential inadvertent treatment effects. Purpose: We describe the methods employed to address the challenges confronted in implementing PUPS. In this randomized controlled trial, we are assessing the efficacy of a complex, preventive intervention in reducing the incidence of, and costs associated with, the development of medically serious pressure ulcers in people with spinal cord injury. Methods: Individuals with spinal cord injury recruited from RLANRC were assigned to either a 12-month preventive intervention group or a standard care control group. The primary outcome is the incidence of serious pressure ulcers with secondary endpoints including ulcer-related surgeries, medical treatment costs, and quality of life. These outcomes are assessed at 12 and 24 months after randomization. Additionally, we are studying the mediating mechanisms that account for intervention outcomes. Results: PUPS has been successfully implemented, including recruitment of the target sample size of 170 participants, assurance of the integrity of intervention protocol delivery with an average 90% treatment adherence rate, and enactment of the assessment plan. However, implementation has been replete with challenges. To meet recruitment goals, we instituted a five-pronged approach customized for an underserved, ethnically diverse population. In intervention delivery, we increased staff time to overcome economic and cultural barriers to retention and adherence. To ensure treatment fidelity and replicability, we monitored intervention protocol delivery in accordance with a rigorous plan. Finally, we have overcome unanticipated assessment and design concerns related to (1) determining pressure ulcer incidence/severity, (2) randomization imbalance, and (3) inadvertent potential control group contamination. Limitations: We have addressed the most daunting challenges encountered in the recruitment, assessment, and intervention phases of PUPS. Some challenges and solutions may not apply to trials conducted in other settings. Conclusions: Overcoming challenges has required a multifaceted approach incorporating individualization, flexibility, and persistence, as well as the ability to implement needed mid-course corrections.